Virtual Simulator for Collaborative Tasks of Aerial Manipulator Robots. - Aguirre, Oscar A. (2022)
This article proposes the development and implementation of a 3D virtual simulator to analyze and observe the behavior of aerial manipulator robots in collaborative control tasks, as well as autonomous and tele-operated navigation through a multi-user room. The virtual environment was developed using 3D photogrammetry which serves as a real scenario to test the collaborative control tasks. The interface for communication between the environment and the aerial manipulator robots is the UNITY 3D graphic engine, which has a bi-directional link with the scientific mathematical software MATLAB, using libraries (DLLs) to provide feedback and compensate for control errors. Finally, the simulation results will be presented and discussed to validate and test the proposed collaborative control strategies.